4 - Excellence, Relevance and the University: The “Missing Middle” in Socio-Economic Engagement - Perry, Beth; May, Tim (Journal of Higher Education in Africa, 2006)
The international political economy for higher education is marked by an increas- ing globalisation and regionalisation of activities. In this context an emphasis on the roles of universities as engines of economic growth and sub-national economic and social development can be seen. However, the de-contextualised nature of domi- nant neo-liberal global pressures gives rise to particular sets of issues for universi- ties and a “missing middle” between contexts of knowledge production and appli- cation. This article explores these issues in comparative context, drawing on empirical work undertaken on regional science policies in Europe and considering the impli- cations for African universities as they seek to fulfil a diverse range of scientific and civic roles. It is structured in three sections. First, it examines the global pressures that are leading to a rethinking and rescaling of science. Second, it analyses chang- ing discourses around excellence, relevance and context and in so doing identifies a convergence in models of national science policy. Finally, it examines the impli- cations for the global university order, including issues of stratification and diversi- fication and a resulting tension that emerges between the expectations of higher education and their capacities to deliver. It is this missing middle that needs consid- eration if expectations and capacity are to be more realistically matched for greater benefit.